Highly efficient and low cost UMP surfactant for crude oil transportation - Hamid Nour, Abdurahman; Rosli, Mohd Yunus; Hamid Nour, Azhary; Mona, Timan; Mohd Arman, Abdul Kadir (2021)
Heavy crude oils have a large share of the world’s potentially recoverable oil reserves. They are characterized by API gravity below 22.3° and possess extremely high viscosity, generally from 1,000 to more than 100,000 mPa·s. Transportation of heavy crude oils through pipelines is highly complex operation, which is still one of the major challenges for petroleum industry, especially in offshore environment (low temperature conditions). Petroleum industries used to avoid production of heavy crude oil reserves due to economic aspects and technical complexities involved with their transportation. However, to meet globally increasing demand of energy, they have started exploration and exploitation of heavy crude oils. In this invention, suitable surfactant (NS-19-02) has been formulated in the laboratory and characterized using standard analytical instruments. Further the formulated surfactant has been utilized to prepare o/w emulsions of heavy crude oils collected from different oil fields. The formulated surfactant characterized as environmentally friendly, economically competitive and technically visible.